2015
DOI: 10.1007/s10529-015-1939-5
|View full text |Cite
|
Sign up to set email alerts
|

In vivo repair of rat transected sciatic nerve by low-intensity pulsed ultrasound and induced pluripotent stem cells-derived neural crest stem cells

Abstract: Combination of LIPUS with iPSCs-NCSCs promoted the regeneration and reconstruction of rat transected sciatic nerve and is an efficient and cost-effective method for peripheral nerve regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 15 publications
1
48
0
Order By: Relevance
“…LIPUS has been shown to have a positive effect on stem cell proliferation. [30][31][32] Three types of mesenchymal stem cells were treated with 1-MHz LIPUS (ET = 5 or 20 minutes, I SATA = 250 or 750 mW/cm 2 ). All MSCs showed different degrees of proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…LIPUS has been shown to have a positive effect on stem cell proliferation. [30][31][32] Three types of mesenchymal stem cells were treated with 1-MHz LIPUS (ET = 5 or 20 minutes, I SATA = 250 or 750 mW/cm 2 ). All MSCs showed different degrees of proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…LIPUS treatment was performed on tissue culture plate or the incision site of the rat, following the procedure previously described (Lv et al, ; Xia et al, ). In brief, LIPUS was generated by a LIPUS apparatus US10 (Cosmogamma, Italy) and transmitted through the bottom of the culture dish or the incision site of the rat via coupling gel (Tianjin Xiyuansi Workshop, China) coated between ultrasonic transducer and dish or the rat skin.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies found that low‐intensity ultrasound (LIPUS) with intensity of 500 mW/cm 2 could promote the proliferation of induced pluripotent stem cells‐derived neural crest stem cells (iPSCs‐NCSCs), enhance the cell viability, and promote iPSCs‐NCSCs differentiation into neurons and Schwann cells (Lv, Zhao, Chen, Sha, & Yang, ). In vivo studies also found that LIPUS combined with iPSCs‐NCSCs treatment can improve the repair of sciatic nerve with 10‐mm injury in rat (Lv et al, ). However, the molecular mechanisms involved in the proliferation and differentiation of iPSCs‐NCSCs after LIPUS treatment are still unclear.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, it has been exhibited that combined application of low‐intensity pulsed ultrasound with iPSCs–neural crest‐derived stem cells can stimulate the regeneration and reconstruction of rat‐transected sciatic nerve (Lv et al, ). However, some important issues need to be considered in order to use iPSCs in nerve tissue engineering, such as differences among iPSC populations in differentiation and expansion stages and selection of the suitable differentiation phase of the cells for desired tissue engineering applications (Wang et al, ).…”
Section: Transplantation Of Cell‐seeded Nerve Conduits For Peripheralmentioning
confidence: 99%